Learning to use the Internet and online social media: What is the effectiveness of home-based intervention for youth with complex communication needs?. (June 2014) - Grace, Emma; Raghavendra, Parimala; Newman, Lareen; Wood, Denise; Connell, Tim
Youth with complex communication needs (CCN) face increased barriers to their social participation due to limited communication abilities and opportunities. Youth today use the internet as a social tool and youth with CCN may also benefit from internet use to increase their social participation. Five youth between the ages of 10–18 with CCN who are unable to use speech for everyday communication and require augmentative and alternative communication were provided with assistive technology and a tailored 1:1 intervention at home to learn to use the internet for connecting with others. Pre and post assessments measured changes in performance on internet use goals, social networks, loneliness and self-concept. Multiple measures were used to examine the impact of internet use for social networking on a range of outcomes and to gather emerging evidence in this area. Results showed that the intervention was effective in increasing performance and satisfaction with goals for increasing internet use to connect with others and for increasing the number of online communication partners. There was no significant change in loneliness or self-concept. This study shows that the internet may be a viable tool in increasing the social participation of youth with CCN. However, some youth and their families required intensive support and technical assistance to gain confidence in internet use and in use for social purposes.